Mapping higher-order relations between brain structure and function with embedded vector representations of connectomes - Gideon Rosenthal (Nature Portfolio, 2018)
The function of a brain region is determined by the network it is embedded in. Here the authors implement the word2vec algorithm for connectomes generating a vector embedding of the connectivity structure for each node allowing inference about functional relationships between brain regions.